Hubungan Sindrom Metabolik dengan Penyakit Ginjal Kronis: Literature Review - Adelia Sephia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The prevalence of metabolic syndrome in the world continues to increase every year. Various studies have been conducted to investigate the impacts of metabolic syndrome. Most studies prove that metabolic syndrome is associated with increased risk of progressive decrease in kidney function and developing chronic kidney disease in the future. The aim of this literature review is to analyze the relationship and pathophysiological mechanisms between metabolic syndrome and chronic kidney disease. The result of this review shows there is a significant relationship between metabolic syndrome and chronic kidney disease. The presence of metabolic syndrome increases the risk of developing chronic kidney disease in the future, quicken the decline of kidney function, and increases risk of mortality. Metabolic syndrome triggers excessive production of pro-inflammatory cytokines and activation of RAAS (renin-angiotensin-aldosterone system) that causes chronic kidney disease. To prevent the incidence of chronic kidney disease in the future, it is necessary to do prevention such as control healthy diet and lifestyle so we do not suffer metabolic syndrome. In addition, it is important to control the components of metabolic syndrome suffered along with improving diet and lifestyle to prevent severity of metabolic syndrome.